Tren dan Pemetaan Digitalisasi dalam Manajemen Sumber Daya Manusia 2018-2026: Analisis Bibliometrik dan Systematic Literature Review - Nur Hasanah; Bhagaskara Adiwidya Bhadra (Jurnal Riset Akuntansi, 2026)
Purpose Research on digitalization in Human Resource Management (HRM) has grown significantly alongside rapid digital transformation and organizational change. However, studies integrating systematic literature review and bibliometric analysis remain limited. This study aims to examine research trends and thematic developments related to digitalization in HRM through a hybrid systematic literature review and bibliometric analysis approach. Method This study employed a Systematic Literature Review based on PRISMA 2020 guidelines using data from the Scopus database with keywords related to digitalization and Human Resource Management. The initial search identified 2,497 documents, and after the screening process, 108 relevant articles were selected. Data were analyzed using VOSviewer to identify publication trends, keyword relationships, collaboration networks, and thematic clusters. Findings The findings indicate that research on digitalization in HRM increased significantly during 2018–2026. Dominant themes include digital transformation, artificial intelligence, e-HRM, innovation, Industry 4.0, sustainability, and organizational performance. Digitalization in HRM has evolved from administrative automation toward strategic organizational transformation supported by technology and data-driven decision making. Originality/value This study integrates systematic literature review and bibliometric analysis to provide a comprehensive understanding of digitalization in HRM.